Kinesin-1 regulates dendrite microtubule polarity in Caenorhabditis elegans - Jing Yan; Dan L Chao; Shiori Toba; Kotaro Koyasako; Takuo Yasunaga; Shinji Hirotsune; Kang Shen (eLife, 2013)
In neurons, microtubules (MTs) span the length of both axons and dendrites, and the molecular motors use these intracellular ‘highways' to transport diverse cargo to the appropriate subcellular locations. Whereas axonal MTs are organized such that the plus-end is oriented out from the cell body, dendrites exhibit a mixed MTs polarity containing both minus-end-out and plus-end-out MTs. The molecular mechanisms underlying this differential organization, as well as its functional significance, are unknown. Here, we show that kinesin-1 is critical in establishing the characteristic minus-end-out MT organization of the dendrite in vivo. In unc-116 (kinesin-1/kinesin heavy chain) mutants, the dendritic MTs adopt an axonal-like plus-end-out organization. Kinesin-1 protein is able to cross-link anti-paralleled MTs in vitro. We propose that kinesin-1 regulates the dendrite MT polarity through directly gliding the plus-end-out MTs out of the dendrite using both the motor domain and the C-terminal MT-binding domain.